Detection of Streptococcus mutans Genomic DNA in Human DNA Samples Extracted from Saliva and Blood. (30th March 2011) - Vieira, Alexandre R.; Deeley, Kathleen B.; Callahan, Nicholas F.; Noel, Jacqueline B.; Anjomshoaa, Ida; Carricato, Wendy M.; Schulhof, Louise P.; DeSensi, Rebecca S.; Gandhi, Pooja; Resick, Judith M.; Brandon, Carla A.; Rozhon, Christopher; et al.
Abstract : Caries is a multifactorial disease, and studies aiming to unravel the factors modulating its etiology must consider all known predisposing factors. One major factor is bacterial colonization, and Streptococcus mutans is the main microorganism associated with the initiation of the disease. In our studies, we have access to DNA samples extracted from human saliva and blood. In this report, we tested a real-time PCR assay developed to detect copies of genomic DNA from Streptococcus mutans in 1, 424 DNA samples from humans. Our results suggest that we can determine the presence of genomic DNA copies of Streptococcus mutans in both DNA samples from caries-free and caries-affected individuals. However, we were not able to detect the presence of genomic DNA copies of Streptococcus mutans in any DNA samples extracted from peripheral blood, which suggests the assay may not be sensitive enough for this goal. Values of the threshold cycle of the real-time PCR reaction correlate with higher levels of caries experience in children, but this correlation could not be detected for adults.